Enkripsi SMS dengan Menggunakan One Time Pad (OTP) dan Kompresi Lempel-Ziv-Welch (LZW) - Fitri Diani; Yudi Widhiyasana (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2018)
Short Message Service (SMS) is one of the features on a mobile phone. This feature is widely used because it is easy to use and does not require the latest telecommunications network connection. Short messages in the form of SMS consistsof 140 characters at the most.The message is sent through infrastructure in telecommunications providers. Using this process, there is a possibility that the sent message is leaked. Therefore, data encryption is required to maintain the message confidentiality. Unfortunately, encryption mechanism uses cipher to encrypt data, which causes another problem. The type of cipher is symmetric or asymmetric, and both cipher mechanism will increase the length of the sent messages. In this paper, One Time Pad encryption method and LZW compression method is used to optimize the message length.